EFFECTIVENESS OF BRANDING WITH LOCAL INDICATORS IN INCREASING OLIVE OIL CONSUMPTION IN VLORA, ALBANIA - Edvina POLAJ; Edmond KADIU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In the area of Vlora, there is no in-depth study on the role of brand with local indicators in olive oil. The purpose of this study is to prove the influence of the brand and local indicators on the development of the olive oil market in Vlora. In this study, the role of the brand with local indicators is analyzed, as is its impact on the increase in the consumption of olive oil and the increase in the income of the agro-processing industries in the study area. Focusing on the market in this area, it is examined how branding with local indicators can influence consumer preferences and increase product consumption. Through the analysis of factors such as price, design with local indicators, quality, and promotion, it is intended to discover the most effective strategy to increase sales of olive oil in the study area. The research was conducted with the participation of over 200 consumers. To analyze the questionnaire, nominal-type econometric models were used, a suitable model to evaluate the impact of products branded with local indicators on the purchasing decisions of consumers. The program used for quantitative data processing is STATA. According to the research findings, it turns out that the brand's local indicators play an important role in the purchase decision. Also, the results of the study provide valuable guidelines for agro-processing industries and decision-makers who should pay special attention to branding with local indicators as an effective strategy to maximize the market potential for olive oil in the study ar